2019
DOI: 10.5194/isprs-archives-xlii-2-w12-103-2019
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Mucous Glands Segmentation in Histological Images

Abstract: <p><strong>Abstract.</strong> Mucous glands is an important diagnostic element in digestive pathology. The first step of differential diagnosis of colon polyps in order to assess their malignant potential is gland segmentation. The process of mucous glands segmentation is challenging as the glands not only needed to be separated from a background but also individually identified to obtain reliable morphometric criteria for quantitative diagnostic methods. We propose a new convolutional neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the gland segmentation category, 25 models were found, and all the models used 165 images of the Warwick QU dataset from the Gland Segmentation in Colon Histology Images (GlaS) challenge in 2015 ( Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The GlaS challenge was a sub-event of the 18th International Conference on Medical Image Computing and Computer-Assisted Intervention (MICCAI) held to solve the problem of gland segmentation [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the gland segmentation category, 25 models were found, and all the models used 165 images of the Warwick QU dataset from the Gland Segmentation in Colon Histology Images (GlaS) challenge in 2015 ( Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The GlaS challenge was a sub-event of the 18th International Conference on Medical Image Computing and Computer-Assisted Intervention (MICCAI) held to solve the problem of gland segmentation [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the teams showed F1-scores up to 0.91, object Dice scores up to 0.89, and object Hausdorff scores up to 45.4 in the offsite dataset (Part A) and similar results in the onsite dataset (Part B) ( Table 1 ) [ 21 , 22 ]. All the studies after the GlaS challenge also used the same dataset and showed better performance: F1-scores up to 0.92, object Dice scores up to 0.91, and object Hausdorff scores up to 39.8 for Part A as well as Part B ( Table 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The continuation of this research will include enhancing the prediction of glands contours maps and evaluating the method on PATH-DT-MSU [16,17] dataset.…”
Section: Discussionmentioning
confidence: 99%
“…The third dataset is the subset of PATH-DT-MSU dataset [6,7], containing 7 H&E whole slide histological images of digestive tract tumors. Each WSI image is a full-thickness fragment of the stomach wall, cut from the surgical material, and includes areas of adenocarcinoma, adjacent areas of visually unchanged lamina propria and the underlying layers of the stomach wall (muscularis mucosae, submucosa, own muscle layer, subserous areas).…”
Section: Used Datamentioning
confidence: 99%